Analisis Perilaku Belanja Online dan Dampaknya terhadap Ekonomi Keluarga: Sebuah Studi Literatur - Sri Rizka Agustina; Nurul Jannah; Shelsy Aulia; Darmawati (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2026)
This study aims to analyze people's online shopping behavior and assess its impact on family economic conditions. The development of digital technology has transformed people's consumption habits, particularly in shopping activities, which are now increasingly practical through online platforms. Easy access, product diversity, and various payment options have made online shopping a dominant trend. However, this convenience also has the potential to foster consumer behavior that impacts financial stability. This study aims to analyze bold shopping patterns and their impact on household financial conditions. The approach used is descriptive qualitative library research, collecting and analyzing data from various scientific journals, articles, and related references. The study findings indicate that online shopping has diverse effects: on the one hand, it offers time and cost savings, but on the other hand, it can lead to waste and indiscipline in family budget management if not supported by adequate self-control. Therefore, an understanding of financial management and digital literacy is crucial to ensure optimal use of technology without harming family economic well-being. Furthermore, this phenomenon requires synergy between digital platform policies and consumer education to mitigate the risk of impulsive buying. This research confirms that psychological factors often outweigh objective needs in digital transactions. As a recommendation, adaptive financial management support strategies are needed for families in this era of disruption to maintain domestic economic resilience against the pressures of a modern lifestyle.